Numerical calculation of scroll compressor geometry and assessment of its delivery - Prezelj, Jurij; Cerkovnik, Nejc (Frontiers in Mechanical Engineering, 2023)
This paper proposes innovative numerical methods for calculating the chamber volumes and tangential leakage gaps in a scroll compressor, a critical aspect of enhancing its performance and efficiency. It proposes two methods, moving away from traditional analytical approaches, and presents a 0D model for mass flow delivery at varying rotational frequencies and discharge pressures. The first method utilizes numerical identification of conjugate points with minimum distance within the fixed and orbiting involute pair to calculate chamber volumes. This approach compensates for integration errors by considering the subareas defined by the normal distance of each involute to the other. The second method simplifies the process by assuming that the line defining the orbital angle intersects the involutes at the conjugate points, with volumes calculated using area discretisation on triangles. Both methods underwent validation against three analytical calculations, showing an agreement within an overall uncertainty error of 3% for the maximum suction volume. The 0D model's results were compared with Ma et al.'s hybrid method and actual measurements. Upon improving Ma's model by accounting for intake air heating and negative pressure in the intake volume, a significant agreement between modelling and measurements was observed. This study concludes that the proposed numerical methods can enhance the accuracy of scroll compressor geometry calculation and mass flow delivery considering tangential gap.